Repeated use of buy-now-pay-later (BNPL) services: A reciprocal relationship of technological and behavioral attributes - Wulandjani, Harimurti (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2026)
This study examines the reciprocal relationship between BNPL usage and consumer attitudes—specifically, perceived security, ease of use, pain of payment, and impulse-buying tendency—and how these attitudes influence subsequent BNPL usage. A time-lagged survey design was implemented with two waves of data collection (Time 1 and Time 2) over a six-month period, involving 357 Indonesian Gen Z consumers. Hypotheses were tested using structural equation modeling (SEM). BNPL usage at Time 1 is positively related to perceived security, ease of use, payment pain, and impulse-buying tendency. Perceived security, ease of use, and impulse-buying tendency, in turn, positively influence BNPL usage at Time 2, whereas payment pain negatively affects future usage. This research contributes to the literature by empirically validating a reciprocal model of BNPL usage that integrates technological and psychological determinants and highlighting the differential role of payment pain in a non-Western, Gen Z context.